Balāghah Studies of Uṣlūb al-Muqābalah in Part 30 of the Holy al-Qur’ān - Aidillah Sujai; Cahya Edi Setyawan (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - The purpose of the research is to know the kinds of uṣlūb al-muqābalah used in al-Qur’ān and know his intention from the balāghah aspect. These research objects are uṣlūb al-muqābalah in al-Qur’ān at part 30 of 24 uṣlūb. Design/methodology/approach - The method used in data collecting is the sheet of library research and literature. The method used in data analysis is Balāghah Descriptive and Content Analysis by using a table. Findings - After research uṣlūb al-muqābalah in al-Qur’ān at part 30, the writer takes conclusion are: 1) The verses become uṣlūb al-muqābalah is 24 uṣlūb. They are 17 uṣlūb from al- muqābalah min ma’nayaini and 7 uṣlūb from al-muqābalah aksar min ma’nayaini. 2) Purpose of uṣlūb al-muqābalah is: a. For beautiful words (All uṣlūb), b. To an explanation of ma’na (14 uṣlūb), c. To emphasizing of ma’na (10 uṣlūb), d. Too easy in memories (all uṣlūb). Originality/value - The benefit of this research is helping Muslims understand al-Qur’ān with uṣlūb al-muqābalah, and finding the miracle of al-Qur’ān. Paper type – Research Paper